Tweeting the economy: Analyzing social media sentiments and macroeconomic indicators - Fitriani, Insi; Amalyah Agus, Anna (Journal of Innovation in Business and Economics, 2023)
This research aims to examine the correlation between social media sentiment and the Consumer Confidence Index (CCI) as well as Gross Domestic Product (GDP) in Indonesia. Data were collected through web scraping from Twitter (now also known as X) spanning from 2019 to 2022 on a monthly basis. Using Pearson and Kendall’s Tau correlation tests, the study found that the correlation between Twitter sentiment and the CCI is not significant. However, there is a significant correlation between Twitter sentiment from news accounts and GDP The findings indicate that the views and perceptions expressed in social media sentiment, particularly from news accounts on Twitter, could serve as an initial indicator of Indonesia's GDP.